MATERNAL RISK FACTORS FOR INTRAUTERINE FETAL DEATH (IUFD) - Ghyiacy, P; Jahanfar, Sh; Mokhtar Shahy, Sh; Haghani, H (Iran University of Medical Sciences, 2002)
Background: Intrauterine fetal death is a traumatic event for the family which occurs in about 1% of all pregnancies. In comparison with other countries this rate is increasing in Iran. Statistical reports from health centers of Firoozabad estimated the rate of 2.2% per year. Although obstetrical management has improved significantly, more than 50% of these cases are still unexplained. Objective: To determine maternal risk factors for intra uterine fetal death. Design: This research was a case-control study. A standard questionnaire was designed consisting of two major parts: maternal characteristic and pre pregnancy and prenatal events. The questionnaire was filled by using medical records, between 1996-2000. And for each given case two controls were chosen simple randomly at the same day. Sample: Samples included 450 records, of which, 150 were case (IUFD) and 300 considered as control group (non IUFD). Results: Findings suggested that, illiterately (P=0.000), gestational age lesser than 37 wk (P=0.000) and consanguinity (P=0.000) were maternal factors. History of stillbirth (P=0.005) and premature rupture of membrane more than 12 hours (P=0.007) were the risk factors related to pregnancy events. Conclusion: According to the results of this study, illiterately, low gestational age, consanguinity, history of stillbirth and premature rupture of membrane were found as maternal risk factors for IUFD, however consultation, prenatal care, early diagnosis of complications, and careful evaluation may decrease the incidence of IUFD. Educating women for IUFD risk factors and use of preventive modalities is also recommended.